A "drop‐wipe‐test" SERS method for rapid detection of pesticide residues in fruits. (6th December 2017) - Wang, Kehui; Huang, Meizhen; Chen, Jie; Lin, Lulu; Kong, Lili; Liu, Xi; Wang, Hui; Lin, Mengshi
Abstract: A simple "drop‐wipe‐test" approach for rapid detection of pesticide residues in fruits was developed based on surface‐enhanced Raman spectroscopy (SERS) coupled with wiper‐type filter paper substrate. The filter paper was coated with silver nanoparticles (Ag NPs) and used as a flexible and absorbent wiper‐type SERS substrate. The first two steps "drop" and "wipe" were combined to simplify the procedures of extraction and sampling of the analyte molecules. "Test" was the last step to obtain the spectral data using a portable Raman spectrometer (Hx‐Spec) developed by our laboratory. The entire detection process was completed just in a few minutes. The optimal wipe time of ~15 s was confirmed used to ensure a thorough extraction of analyte molecules. The as‐prepared SERS substrate was used for rapid detection of pesticide residue (i.e., thiram) in apple, pear, and grape by "drop‐wipe‐test" method. Results demonstrate that the concentrations of thiram spiked on the three fruits skin show a linearly relationship with the average intensity ( n  = 7) of SERS spectra with R ‐square values of 0.9991, 0.9872, and 0.9841, respectively. The limit of detection of thiram in apple, pear, and grape peel was 4.6261, 5.1799, and 5.7061 ng/cm 2, respectively. The detection limits are all below the maximum residue limits for pesticide in food that were set by the National Food Safety Standard of China (GB). The results demonstrate that SERS method coupled with a flexible and absorbent SERS substrate can be used as a practical application for a reliable, rapid, and sensitive detection of pesticide residues. Abstract : A simple "drop‐wipe‐test" approach for rapid detection of pesticide residues in fruits was developed based on surface‐enhanced Raman spectroscopy (SERS) coupled with wiper‐type filter paper substrate. The flexible and absorbent filter paper was coated with silver nanoparticles (Ag NPs). The performance of the substrate and the optimal wipe time were investigated. The limit of detection of thiram in apple, pear, and grape peel was 4.6261, 5.1799, and 5.7061 ng/cm 2, respectively.